Rebalancing interests and power structures on crowdworking platforms - Ayad Al-Ani; Stefan Stumpp (Internet Policy Review, 2016)
Crowdwork on virtual platforms is developing into a recognisable employment and business model on the internet. Despite their many differences, the platforms that have emerged over the last few years have one thing in common: a crowd of individual producers and capabilities is mobilised – in the form of labour, accommodation or durable goods – onto the market in cooperation and competition with firms from traditional industries. This study analyses the factors crowdworkers consider relevant in their work and the measures they view as helpful in improving their working relationship with platforms. It is apparent that, in the best tradition of the peer economy, this new type of worker still considers learning and fun important factors for his or her engagement. Despite these effectively intrinsic factors, workers are quite aware of their situation, which does not put them on equal terms with the platform's algorithms and customer focus. This awareness of power disparities does not lead them, however, to reconsider their effectiveness when it comes to renegotiating terms with the platform: when specifically asked about the role of unions, the majority of crowdworkers did not expect help in self-organisation from these institutions. Considering the difficulties in regulating the market for platforms, (self-) organisation of crowdworkers, however, is an important prerequisite in rebalancing the power structure dominated by platform owners and their customers. Self-organisation is something digital natives are quite familiar with and we have to assume that crowdworkers are perhaps overconfident in their abilities. And due to the novelty of this industry, this confidence has not been shaken yet by labour disputes or even by growing dissatisfaction with platforms.
Keywords: 300; Crowdworking; Crowdsourcing; Sharing economy